2021
DOI: 10.2147/ijn.s289107
|View full text |Cite|
|
Sign up to set email alerts
|

Modulating the Biomechanical Properties of Engineered Connective Tissues by Chitosan-Coated Multiwall Carbon Nanotubes

Abstract: Background Under certain conditions, the physiological repair of connective tissues might fail to restore the original structure and function. Optimized engineered connective tissues (ECTs) with biophysical properties adapted to the target tissue could be used as a substitution therapy. This study aimed to investigate the effect of ECT enforcement by a complex of multiwall carbon nanotubes with chitosan (C-MWCNT) to meet in vivo demands. Materials and Methods ECTs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Depending on the molecular composition and the method of preparation, various nanostructures of various sizes could be generated . Self-assembled nanomaterials have been applied in a variety of scientific fields such as electronics, photonics, biology, and medicine. , In medicine, self-assembled nanomaterials can be applied in tissue engineering, , cancer immunotherapy, biosensing, antimicrobial therapy, , anti-inflammatory drugs, , the development of vaccines, and novel drug delivery systems. , Many kinds of research have been developed to improve the properties of existing drugs by enhancing the water solubility of poorly soluble therapeutics, decreasing drug toxicity, improving drug pharmacokinetic profiles, and also developing a sustained release system of drugs . One of the most studied anticancer drugs is doxorubicin (DOX), which inhibits cancer growth by interrupting the topoisomerase II enzyme that is responsible for DNA replication and transcription .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the molecular composition and the method of preparation, various nanostructures of various sizes could be generated . Self-assembled nanomaterials have been applied in a variety of scientific fields such as electronics, photonics, biology, and medicine. , In medicine, self-assembled nanomaterials can be applied in tissue engineering, , cancer immunotherapy, biosensing, antimicrobial therapy, , anti-inflammatory drugs, , the development of vaccines, and novel drug delivery systems. , Many kinds of research have been developed to improve the properties of existing drugs by enhancing the water solubility of poorly soluble therapeutics, decreasing drug toxicity, improving drug pharmacokinetic profiles, and also developing a sustained release system of drugs . One of the most studied anticancer drugs is doxorubicin (DOX), which inhibits cancer growth by interrupting the topoisomerase II enzyme that is responsible for DNA replication and transcription .…”
Section: Introductionmentioning
confidence: 99%
“… 3 Self-assembled nanomaterials have been applied in a variety of scientific fields such as electronics, photonics, biology, and medicine. 1 , 4 7 In medicine, self-assembled nanomaterials can be applied in tissue engineering, 8 , 9 cancer immunotherapy, 10 biosensing, 11 antimicrobial therapy, 12 , 13 anti-inflammatory drugs, 14 , 15 the development of vaccines, and novel drug delivery systems. 16 , 17 Many kinds of research have been developed to improve the properties of existing drugs by enhancing the water solubility of poorly soluble therapeutics, decreasing drug toxicity, improving drug pharmacokinetic profiles, and also developing a sustained release system of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…In work developed by Kittana et al, 48 MWCNTs were used together with chitosan, C-MWCNTs, for physiological repair of connective tissues with biophysical properties adapted to the target tissue, denominating optimized engineered connective tissues (ECTs). In this work, one started with human fibroblasts (HFF-1) in collagen type I enriched with three different percentages (0.025, 0.05, and 0.1%) of C-MWCNT.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…49 Studies have shown that CNTs promote proliferation of osteoblasts and bone formation, therefore representing an enormous technological advancement in the field of bioengineering. 50,51 Additionally, the association of CNTs with other polymers, whether natural or synthetic, improves the mechanical properties of these polymers, 47,48 resulting in more resistant biocomposites with greater capacity for increased nucleation and growth of hydroxyapatite crystals, 47,48 when compared to the use of polymers in isolation. The literature focuses on the study of CNTs in the research on CNT scaffolds for bone regeneration, 52 Figure 3.…”
Section: Carbon Nanotubesmentioning
confidence: 99%